High-Velocity Oxygen Fuel (HVOF) Reinforcement of Amorphous Materials: A Pathway to Superior Wear and Corrosion Resistance - Emilia DOBRIN; Alin-Constantin MURARIU (INCAS Bulletin)
The escalating demand for advanced structural materials with superior wear and corrosion resistance in aeronautical and military applications has spurred interest in amorphous alloys, particularly metallic glasses, due to their non-crystalline atomic configurations and exceptional mechanical properties. High-Velocity Oxygen Fuel (HVOF) spraying, a high-performance thermal spray technology, has emerged as a robust solution for enhancing the surface integrity of these materials by delivering dense, well-bonded coatings. This study investigates the integration of HVOF in reinforcing amorphous materials, with a specific focus on augmenting wear resistance under extreme mechanical stresses and improving corrosion protection in hostile environments. Key parameters such as particle velocity, flame temperature, and spray distance are analyzed to optimize coating quality while preserving the amorphous phase. The article delves into the microstructural evolution during deposition, assessing the resultant performance improvements through empirical data and computational models. Findings indicate that HVOF reinforcement significantly enhances the operational longevity of amorphous materials, positioning them as viable candidates for high-stress, corrosive conditions in military aviation, defense systems, and aerospace components.